Radio‐cephalic fistula recovered with drainage to median basilic vein by straightening of the forearm cephalic vein: A case report. Issue 6 (24th May 2022) - Costa, Luísa Lemos; de Matos, António Norton; Almeida, Paulo; Teles, Paulo; Loureiro, Luís; Campos, Luís; Delgado, Elisabete; Oliveira, Debora; Campos, Tiago; Inácio, Marta; Fernandes, Filipa; Coutinho, Sara; et al.
Abstract: The distal arteriovenous fistula (AVF) has less complications and better patency than the proximal fistula, when it works properly. The complications of outflow of the fistula are complex, and it is necessary to analyze all solutions to solve the problem. We introduce a novel approach to solve outflow problems of a radio‐cephalic AVF by straightening of the forearm cephalic vein with drainage into the median basilic vein.